2022
DOI: 10.3390/children9091334
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Coverage in Children Younger Than 1 Year of Age during Periods of High Epidemiological Risk: Are We Preparing for New Outbreaks?

Abstract: Background: According to WHO, infectious disease control can be achieved if the vaccine coverage (VC) exceeds 90%. In recent years there has been a declining trend in VC which could lead to the recurrence of infectious diseases. Objectives: The study analyzed the determinants of VC and of parental decisions regarding immunization in children aged 0–1 year monitored during two high-risk epidemiological periods (the measles epidemic and the COVID-19 pandemic period). Methods: A retrospective observational cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Many factors were described as able to shape the PWs attitude regarding immunization during pregnancy: lack of knowledge regarding the risk of infectious diseases, lack of a national awareness programme for PWs, lack of adequate counselling from the physicians’ teams who take care of the pregnancy, fear of a vaccines’ composition, fake news or vaccine safety issues. International data show variable uptake rates (between 0–78%) for anti-pertussis vaccination in PWs [ 19 , 20 , 21 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors were described as able to shape the PWs attitude regarding immunization during pregnancy: lack of knowledge regarding the risk of infectious diseases, lack of a national awareness programme for PWs, lack of adequate counselling from the physicians’ teams who take care of the pregnancy, fear of a vaccines’ composition, fake news or vaccine safety issues. International data show variable uptake rates (between 0–78%) for anti-pertussis vaccination in PWs [ 19 , 20 , 21 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite much controversy around the subject of PWs immunization, the large majority of the medical staff counsels PWs in a pro-immunization manner. We must admit that a small part of healthcare professionals, maybe not involved directly in the immunization process, may show a hesitant attitude regarding PWs vaccination [ 45 , 46 , 49 ]. Not all specialties’ curricula include immunization classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted by Fathi et al and Mohsen et al, it was found that physicians and health staff were effective in promoting preventive behaviors [35,42]. Physicians were also identified as the most important source of information, and educational programs had an important influence on the behavior of the parents concerning treating or preventing children's diseases [43][44][45]. The study conducted by Biezen et al shows that communication between GPs and parents is therefore a vital component in reducing antibiotic prescribing in general practice [46].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the vaccine coverage during the first year of the COVID-19 pandemic (2020) with the vaccination coverage during the 2019 measles epidemic, a significant decline was observed for all vaccines included in the Romanian National Immunization Program. According to a recent study comparing the general vaccine coverage in children younger than 1 year of age from January 2019 to June 2019 (the measles epidemic) and January 2020 to June 2020 (the COVID-19 pandemic), the measles–mumps–rubella vaccine coverage for administration at the age of 12 months was 64.29% in 2019 vs 55.88% in 2020, and for the diphtheria–tetanus–pertussis vaccine, it was 71.59% in 2019 vs 62.08% in 2020 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%